Dyeing properties of PSA/MPIA blended yarn. Issue 5 (19th August 2014) - Cui, Shuling; Dou, Chunxiao
Abstract : Purpose: To study the dyeing properties of polysulphonamide (PSA)/aramid 1313 (MPIA) blended yarn by selecting suitable dyes and carriers required in the dyeing process. Design/methodology/approach: Dyeing the blended yarn with cationic dyes, acid dyes, disperse dyes, reactive dyes and pigment, and comparing the shades, K/S values and fastness of the blended yarns. Findings: The PSA/MPIA blended fibre is suitable for dyeing with the cationic dye at high temperature and pressure in the presence of carrier acetophenone, and good homochromatism are showed on the two fibres when using same type of dye. Originality/value: Polysulphonamide fibre is a thermo-resistant and flame-retardant product made in China in recent years. Blended with aramid 1313 fibre, it may acquire good spinnability. But there is little technical report about properties of the blended yarn in the literature at present. This paper reports the dyeing property of such fibres for the first time.